12. OUTCOMES AFTER SURGICAL RESECTION OF MELANOMA BRAIN METASTASES IN THE AGE OF CHECKPOINT INHIBITOR TREATMENT. (4th August 2020) - Morshed, Ramin; Chung, Jason; Sudhakar, Vivek; Cummins, Daniel; Young, Jacob; Daras, Mariza; Aghi, Manish
Abstract: BACKGROUND: Metastasis of melanoma to the brain is associated with poor outcomes. Recent trials demonstrate improved survival after treatment with immune checkpoint inhibitors. OBJECTIVE: To examine the impact that checkpoint inhibitor treatment has on overall survival (OS) and central nervous system (CNS) progression in a cohort of patients undergoing surgical resection of melanoma brain metastases. METHODS: This retrospective, single-center study included patients undergoing first-time surgical resection of melanoma brain metastases. A multivariate Cox proportional model was used to estimate the association of patient and treatment factors with OS and CNS progression. RESULTS: 85 patients underwent first-time resection of 97 melanoma brain metastases with a median follow-up of 9.5 months. Checkpoint inhibitors (Pembrolizumab, Ipilimumab, and/or Nivolumab) were used in 55.1% of cases (19 pre-op; 47 post-op; median 9 cycles). Patients treated with checkpoint inhibitors had similar peri-op systemic disease status and KPS but had been treated with more systemic agents and had more instances of CNS progression prior to surgery. Median OS and time to CNS progression for the cohort were 1 year and 237 days, respectively. In a multivariate Cox regression model, age (HR 1.03 by decade; p=0.02), treatment with a checkpoint inhibitor (HR 0.27; p<0.0001), prior radiotherapy (HR 2.44; p=0.007), and number of brain metastases at the time of surgery (HR 1.05 per metastasis; p=0.04) were significant predictors of OS. Checkpoint inhibitor treatment was associated with longer OS from surgery (median 3 vs 0.5 yrs, log-rank p=0.004). However, patients who underwent craniotomy after prior checkpoint inhibitor treatment had poor OS (median 0.56 yrs). Prior radiotherapy was also associated with poor OS (median 0.53 yrs). CONCLUSIONS: While checkpoint inhibitor treatment was associated with improved survival in this surgical cohort of melanoma brain metastases, patients who require surgical resection after checkpoint inhibitor treatment or radiotherapy are poor surgical candidates.